Influencia de la cultura organizacional en el desempeño laboral de los trabajadores la empresa "P & D Andina S.A. Jequetepeque" - Cruz Miranda, Alicia Alejandra (2016)
The aim of this study was to analyze the organizational culture and its relationship to job performance of staff assigned to P & D Andina field research was conducted descriptive level, with a population of 70 people applied purposive sampling being comprised 60 people. The results were presented in statistical tables with absolute and percentage numbers, which brought different conclusions among which are: P & D Andina. has a kind of bureaucratic culture, but weak, there is a high turnover of staff which does not allow them to have full knowledge of the existing culture, it was determined that the correlation between organizational culture and job performance, they are two variables that go together to make the personnel are an integral part of the organization, there is business competitiveness and to achieve organizational goals and objectives already raised. Taking into account some factors that would have to be reinforced research identified a number of recommendations in order to improve the job performance venue and the existing culture.